Effect of Academic Stress on Physiological and Biochemical Parameters among Medical Students - Sammar, Kinza; Shah, Inayat; Shah, Maheen; naz, Raeesa; nazir, usman (ADVANCES IN BASIC MEDICAL SCIENCES, 2021)
Objective The primary aim of this study was to understand the effects of a stressed academic environment in medical students through evaluating different physical and biochemical parameters. Methodology This study is longitudinal and based on a convenient sampling method, including 50 volunteer medical students of Ayub Medical College, Abbottabad with mean age 21-25yrs (24±1) in both stressed and unstressed states. Physical and biochemical parameters were evaluated by measuring serum Cortisol and plasma Serotonin levels by using ELISA kits. Data were analyzed by using SPSS- 22. Results Results showed an insignificant difference of Serum Cortisol (6.6±4.2ug/dl) in stressed and (7.0±4.7ug/dl) unstressed states with (p=0.72). , plasma serotonin values in stressed (149±140ng/ml) and unstressed (125±108ng/ml) with (p =.47) Parameters like blood pressure (both systolic and diastolic) with a p-value of <.01 showed significant difference during the examination. However, other variables like Age, Height, Weight, BMI (p= .946), Heart Rate (p= .149) showed no significant difference. Conclusion The study concludes that little to moderate levels of changes of serum cholesterol and plasma serotonin values may occur due to the academic pressure on students, which can affect their professional capabilities Key words Academic stress, Body Mass Index, Serum Cortisol, Plasma Serotonin, ELISA